Assessing the prospective environmental performance of hydrogen from high-temperature electrolysis coupled with concentrated solar power. (August 2022) - Puig-Samper, Gonzalo; Bargiacchi, Eleonora; Iribarren, Diego; Dufour, Javier
Abstract: Hydrogen is currently being promoted because of its advantages as an energy vector, its potential to decarbonise the economy, and strategical implications in terms of energy security. Hydrogen from high-temperature electrolysis coupled with concentrated solar power (CSP) is especially interesting since it enhances the last two aspects and could benefit from significant technological progress in the coming years. However, there is a lack of studies assessing its future environmental performance. This work fills this gap by carrying out a prospective life cycle assessment based on the expected values of key performance parameters in 2030. The results show that parabolic trough CSP coupled with a solid oxide electrolyser is a promising solution under environmental aspects. It leads to a prospective hydrogen carbon footprint (1.85 kg CO2 eq/kg H2 ) which could be classified as low-carbon according to current standards. The benchmarking study for the year 2030 shows that the assessed system significantly decreases the hydrogen carbon footprint compared to future hydrogen from steam methane reforming (81% reduction) and grid electrolysis (51%), even under a considerable penetration of renewable energy sources. Highlights: Life-cycle profile of renewable hydrogen from solid oxide electrolysis in 2030 is assessed. A simulation model with concentrated solar power integration is built for data supply. Prospective carbon footprint shows that hydrogen from this system qualifies as green. In solar-only mode, solar infrastructure becomes an environmental hotspot. Solar plant scale arises as a key factor affecting the life-cycle profile of hydrogen.